Komunitas iman sebagai ruang formasi moral: Reinterpretasi pendekatan “praksis bersama” Thomas Groome bagi pendidikan Kristiani multikultural Indonesia - Woenardi, Thinna Naftali (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2026)
Christian education in multicultural Indonesia faces distinctive challenges in moral formation amidst religious, ethnic, and cultural diversity. This article reinterprets Thomas Groome's